2020
DOI: 10.1016/j.scitotenv.2020.140437
|View full text |Cite
|
Sign up to set email alerts
|

Do rainfall characteristics affect the export of copper, zinc and synthetic pesticides in surface runoff from headwater catchments?

Abstract: Rainfall and runoff characteristics may influence off-site export of pesticides into downstream aquatic ecosystems. However, the relationship between rainfall characteristics and pesticide export from small headwater catchments remains elusive due to confounding factors including the application dose and timing and the variation of pesticide stocks in soil. Here we examined the impact of rainfall characteristics on the export of copper (Cu), zinc (Zn) and 12 legacy and currently used synthetic pesticides in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…In contrast to the above-mentioned factors, the discharge transported through the inlets per event did not appear as a significant influencing factor in the model. This aligns well with a study by Imfeld et al ( 2020 ) reporting that the event concentrations at the outlet of a small vineyard catchment were related to the timing of pesticide applications, but not to characteristics of the rain events.…”
Section: Resultssupporting
confidence: 92%
“…In contrast to the above-mentioned factors, the discharge transported through the inlets per event did not appear as a significant influencing factor in the model. This aligns well with a study by Imfeld et al ( 2020 ) reporting that the event concentrations at the outlet of a small vineyard catchment were related to the timing of pesticide applications, but not to characteristics of the rain events.…”
Section: Resultssupporting
confidence: 92%
“…In earlier studies, Lange et al (2011) and observed a 15 %-30 % mass loss of the fluorescent tracer sulforhodamine-B in the wetland subsection of the current VTS. These results indicate a general potential for sorption of organic compounds in this system but represent an earlier succession state of the wetland and stationary flow conditions with much longer residence times.…”
Section: Contaminant Mass Removalmentioning
confidence: 69%
“…Such systems temporally retain polluted waters and thus provide space, time, and favorable conditions for degradation processes. VTSs studied in literature include very different types of systems (Lange et al, 2011), including vegetated ditches or detention ponds with hydraulic residence times (HRT) ranging in the order of minutes to several hours (Bundschuh et al, 2016;Elsaesser et al, 2011;Ramos et al, 2019) or constructed wetlands in which HRT may reach several weeks (Maillard and Imfeld, 2014), particularly when operated in batch mode (Tournebize et al, 2017;Maillard et al, 2016;Moore et al, 2000). The term "pesticide mitigation" can refer to contaminant mass removal (R M ) or peak concentration reduction (R C ).…”
Section: Introductionmentioning
confidence: 99%
“…Nanocarriers with good biocompatibility have been applied extensively in promoting the translocation of drugs across cell membranes for disease treatment. , Similar to medical therapy, some nanoparticles have been used to construct a pesticide delivery system in recent years, and the controlled release of active ingredients (AIs) is particularly important to obtain the maximum biological efficacy and decrease the negative environmental impacts. Generally, many kinds of adjuvants such as organic solvents, emulsifiers, and dispersants are added to commercial pesticides to increase their biological activity, and large proportions of sprayed pesticides are lost due to photolysis, surface runoff, and spray drift, thus leading to serious environmental pollution and threatening human health. The AIs of most traditional pesticides are hydrophobic, and the AIs can be encapsulated in nanoparticles or attached to the peripheral groups of nanoparticles, which can increase the dispersion and wettability of AIs, and improve stability of AIs against harsh environmental conditions. Our group has constructed a series of dendrimer-based nanoparticles consisting of a fluorescent core and periphery amino groups, which can act as a dsRNA/drug carrier to efficiently improve their delivery efficiency. Furthermore, we construct a star polymer (SPc) without a fluorescent core for large-scale application, which is applied to produce nanoscale botanical/chemical insecticides and increase their insecticidal activity. , …”
Section: Introductionmentioning
confidence: 99%